2020
DOI: 10.1097/hjh.0000000000002410
|View full text |Cite
|
Sign up to set email alerts
|

Self-blood pressure measurement as compared to office blood pressure measurement in a large Indian population; the India Heart Study

Abstract: Objective: India Heart Study (IHS) is aimed at investigating the agreement between office blood pressure measurement (OBPM) and self (S)BPM in a hypertension-naive population. Methods: A total of 18 918 individuals (aged 42.6 ± 11.7 years, 62.7% men), visiting 1237 primary care physicians across India, underwent OBPM. They performed SBPM for a period of 1 week using a validated oscillometric BP monitor that was preprogrammed to adhere to a guideline-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…10 Reported prevalence of higher resting heart rate is in line with the recently published India Heart study which has reported higher average resting heart rate of 80 beats per minute in Indian patients with hypertension. 11 Available Indian epidemiological data suggests the ongoing epidemic of uncontrolled hypertension, strongly leading to various CV complications. Almost 71% higher risk of death attributable to cerebrovascular disease and around 31% higher risk of death attributable to CVD in uncontrolled hypertensives in India.…”
Section: Resultsmentioning
confidence: 99%
“…10 Reported prevalence of higher resting heart rate is in line with the recently published India Heart study which has reported higher average resting heart rate of 80 beats per minute in Indian patients with hypertension. 11 Available Indian epidemiological data suggests the ongoing epidemic of uncontrolled hypertension, strongly leading to various CV complications. Almost 71% higher risk of death attributable to cerebrovascular disease and around 31% higher risk of death attributable to CVD in uncontrolled hypertensives in India.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence supported to look for the use of antihypertensive drugs with HR-lowering effects in Indian patients with hypertension. 12 In case of HF, SO is (i) directly related to the severity of symptoms and thus with the New York Heart Association (NYHA) functional class; (ii) inversely related to measures of left ventricular function, such as left ventricular stroke work, stroke volume, and ejection frac-tion; and (iii) independent of the ischemic or idiopathic nature of the disease. 13…”
Section: Sympathetic Overdrive and Its Key Clinical Impactmentioning
confidence: 99%
“…A vast body of international evidence shows HBPM to have a superior prognostic value and as a better predictor over CBP for CVD outcomes and target organ damage 21 . A finding from the India Heart Study which investigated the agreement of two visits CBP and 7 days home blood pressure (HBP) showed poor agreement between the two readings, and stated the conclusion that when it comes to diagnosing hypertension, HBP should be the preferred method 22 . Summarizing the evidence thus far, HBPM appears to provide close to the true value of an individual's BP control better than CBP, while it shows benefit over ABPM as the patient can measure their BP multiple times for long period on several occasions at their own convenience 19–20 .…”
Section: Introductionmentioning
confidence: 99%